Pemahaman Orangtua Terhadap Kurikulum Merdeka PAUD: Kurikulum Merdeka - putri, putri utami (Universitas Tangerang Raya, 2024)
The implementation of the Kurikulum Merdeka (Independent Curriculum) in early childhood education (PAUD) is a strategic step towards improving the quality of education in Indonesia. This study aims to understand the perspectives of teachers and parents in supporting the implementation of the Kurikulum Merdeka in PAUD. A qualitative approach was employed, utilizing interviews and literature review methods. The results show variations in understanding and support for the Kurikulum Merdeka between teachers and parents. Key factors such as teacher training, school readiness, and parental involvement are crucial for effective implementation. This study provides recommendations for stakeholders to enhance collaboration in supporting the Kurikulum Merdeka.